Genetic recombination of bovine viral diarrhea virus subgenotype -1a and -1c in persistently infected dairy cattle - Sri Handayani Irianingsih; Bagoes Poermadjaja; Hastari Wuryastuti; Raden Wasito (Indonesian Journal of Biotechnology, 2020)
The bovine viral diarrhea virus (BVDV) is a major viral pathogen in cattle worldwide. In Indonesia,  diversity in subgenotypes of BVDV-1 has been observed, with the highest proportion of subgenotype -1a, followed by -1c, -1b, and -1d. So far, phylogenetic analysis of BVDV-1 is based on nucleotide sequences of the 5′ UTR and partial NS5B regions. Accuracy in identifying the subgenotype and antigenic type is critical for vaccine development and effective vaccination. The aim of this study was to determine genetic recombination of BVDV through phylogenetic analysis of five different regions (5′ UTR, NPro, E2, NS3, and NS5B) of BVDV in persistently infected dairy cattle. Five isolates were sequenced using next-generation sequencing, and data were analyzed with the CLC Genomic Workbench 9.0 and MEGA-X programs. Phylogenetic analysis based on the 5′ UTR (275 nt), NPro (504 nt), E2 (1,122 nt), NS3 (2,049 nt), and NS5B (2,157 nt) regions indicated  that one BVDV isolate from Banyumas, Central Java, could be classified into different subgenotypes based on the E2 region (-1c), but the same subgenotype based on the other four regions (-1a), suggesting  the presence of genetic recombination of the BVDV subgenotypes -1a and -1c in persistently infected dairy cattle.